High-strength supported noble metal catalyst as well as preparation method and application thereof
By introducing additives and binders into the support, acidification treatment and hydrothermal impregnation are carried out, the acid resistance and water resistance of the catalyst are improved, and the problem of catalyst strength decreases in HCl catalytic oxidation reaction is solved, and high activity and long life are achieved. Supported precious metal catalysts maintain efficient HCl oxidation reaction conversion rate.
Patent Information
- Application Number
- CN202411207340.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-13
AI Technical Summary
In HCl catalytic oxidation reaction, the catalyst decreases strength due to the impact of high concentration of HCl and moisture, and the powdering and bed pressure drop, affecting the service life of the catalyst and the stability of the reactor.
By introducing additives and binders into the support, acidification and hydrothermal impregnation are carried out to improve the acid and water resistance of the support, and molding is carried out using a twin-screw extruder to enhance the mechanical strength and catalytic activity of the catalyst.
The catalyst has achieved high strength and high activity in high HCl and water vapor environments, extended its service life, maintained a conversion rate of HCl oxidation reaction of more than 90%, and remained basically stable after 200 hours of deterioration treatment. .
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts and relates to a supported noble metal catalyst, in particular to a high-strength supported noble metal catalyst and a preparation method, and application of the catalyst in HCl catalytic oxidation. Background Art
[0002] Supported precious metal catalysts have the advantages of high activity and stable reaction, and have been industrially applied in the industry of HCl oxidation catalysis to produce chlorine.
[0003] Limited by the structural limitations of the fixed bed reactor, the catalyst at the top of the tube is most strongly impacted by the reaction gas. HCl, O2, H2O and non-condensable gas have different degrees of impact on the operation of the catalyst. Among them, the impact of high-concentration HCl and H2O at the inlet on the catalyst is the most obvious. After long-term operation, the unloaded catalyst will show a decrease in strength. In severe cases, it will cause the catalyst to pulverize, which will lead to problems such as increased pressure drop in the reactor bed, difficulty in temperature control, and increased hydrochloric acid impurities in the downstream. It can be seen from this that the catalyst should have sufficient mechanical strength to prevent it from breaking or pulverizing during operation and shortening the catalyst life (Catalysis Today, 1999, 51 (1): 73-84).
[0004] The strength of the catalyst is closely related to the carrier. The main preparation methods of the carrier include: neutralization precipitation method, mechanical mixing method, sol-gel method, hydrothermal synthesis method and thermal decomposition method. The mechanical strength of the carrier obtained by different methods is different. Researchers have done a lot of work to improve the strength of the catalyst. For example, in patent CN202010956355.3, the formed titanium silicon molecular sieve catalyst is hydrothermally treated with a boron-containing aqueous solution, which can effectively improve the mechanical strength of the catalyst; the literature (Industrial Catalysis, 2022, 30(03) :49-52), by adjusting the synthesis conditions, alumina carriers with various pore structures and mechanical strengths are prepared; in patent CN202310989470.4, the prepared high-strength catalyst composite carrier is a "dual-core" spherical structure, the inner core is alumina ball, and the outer core is a high-strength carbon ball, which has the advantages of high strength and low wear; in addition, in the literature (Powder Technology, 2019, 352: 79-90), the mechanical properties and mechanical reliability of the molded catalyst are improved by optimizing the binder / peptizer content and the extrusion speed.
[0005] In the HCl catalytic oxidation reaction, the catalyst at the reactor inlet faces the problem of reduced strength due to high raw gas concentration, high moisture content and large heat release. The strength and durability of precious metal catalysts will inevitably become a key problem restricting their industrial promotion and production. Summary of the invention
[0006] In view of this, the present invention aims to provide a high-strength supported precious metal catalyst and a preparation method thereof, so as to solve the problem that the catalyst at the reactor inlet is subjected to the impact of HCl / H2O and the violent heat release, resulting in the decrease of catalyst strength, partial pulverization, and increase of bed pressure drop, thereby providing a stable and high-strength catalyst for the efficient catalytic production of chlorine by HCl.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] In the present invention, additives, binders, and extrusion aids are introduced into the carrier to modify its structure to improve the carrier strength, and acid treatment is performed to enhance the acid resistance of the carrier in HCl atmosphere. In addition, the noble metal is impregnated by hydrothermal method to enhance the water resistance of the catalyst in water vapor. In particular, the catalyst can be used for the reaction of HCl catalytic oxidation to produce chlorine while having high catalytic activity.
[0009] In one aspect, the present invention provides a method for preparing a high-strength supported noble metal catalyst, comprising the following steps:
[0010] 1) dissolving aluminum chloride, titanium sulfate, zirconium oxychloride and additives in a solvent, adding ammonia water for precipitation, controlling the pH value of the solution, standing for aging, filtering, washing, drying and calcining to obtain carrier-1;
[0011] 2) soaking the carrier-1 prepared in step 1) in a weakly acidic solution, taking it out and drying it to obtain a pretreated carrier-2;
[0012] 3) Carrier-2, binder, extrusion aid and water are mixed and kneaded uniformly, and then loaded into a twin-screw extruder, molded using a template, and dried to obtain carrier-3;
[0013] 4) Finally, water is added to the carrier-3 and the noble metal precursor solution to mix evenly to obtain a mixed solution, which is then transferred to the inner lining of a hydrothermal reactor, hydrothermally impregnated in a high-temperature oven, and then dried and air-baked to obtain a high-strength supported noble metal catalyst.
[0014] In the present invention, the mass ratio of the aluminum chloride, titanium sulfate and zirconium oxychloride in step 1) is 0.41-4.49:3.58-6.24:1, preferably 1.6-1.7:4.7-4.8:1.
[0015] In the present invention, the mass ratio of aluminum oxide, titanium oxide and zirconium oxide in the carrier-1 in step 1) is 0.41-4.5:1.95-3.4:1, preferably 1.6-1.7:2.5-2.7:1.
[0016] In the present invention, the additive in step 1) is selected from any one or more of sodium silicate, boric acid, magnesium chloride, zinc chloride, and copper sulfate, preferably sodium silicate.
[0017] In the present invention, the mass ratio of the additive to aluminum chloride in step 1) is 1:45-55.
[0018] In the present invention, the solvent in step 1) is water, and the concentration of the aqueous ammonia is 0.45 to 0.55 mol / L.
[0019] In the present invention, the pH value of the solution in step 1) is 8 to 10, preferably 8.5 to 9.5.
[0020] The standing time is 12 to 24 hours, preferably 16 to 20 hours.
[0021] In the present invention, the filtering method described in step 1) is reduced pressure filtration.
[0022] In the present invention, the washing solution in step 1) is selected from water or ethanol, preferably water and ethanol are used in combination, and there is no particular limitation on the number of washings, preferably 1 to 5 times of water washing and 1 to 5 times of ethanol washing.
[0023] In the present invention, the drying temperature in step 1) is 60-80° C., preferably 68-72° C., and the drying time is 8-16 hours, preferably 11-13 hours.
[0024] The calcination temperature is 800-1200° C., preferably 950-1050° C., and the calcination time is 3-7 hours, preferably 4.5-5.5 hours.
[0025] In the present invention, the calcination in step 1) is carried out in a gas atmosphere, the gas is selected from nitrogen, an inert atmosphere or an oxidizing gas, the inert atmosphere is selected from one or both of argon and helium, and the oxidizing gas is selected from oxygen and air, preferably air.
[0026] In the present invention, the weak acid solution in step 2) is selected from any one or more of hypochlorous acid, phosphoric acid, citric acid, formic acid, and acetic acid, preferably hypochlorous acid; the concentration of the weak acid solution is 0.04 to 0.06 mol / L.
[0027] In the present invention, the immersion in step 2) is a conventional operation in the art, and the amount of the solution is not particularly limited, as long as the carrier-1 can be immersed therein. The mass ratio of the carrier-1 to the weakly acidic solution is 1:1-3, preferably 1:1.5-2.5.
[0028] In the present invention, the soaking in step 2) is carried out at a temperature of 20 to 30° C., preferably 24 to 26° C., for a time of 4 to 12 hours, preferably 7 to 9 hours.
[0029] In the present invention, the drying in step 2) is carried out at a temperature of 60 to 80° C., preferably 68 to 72° C., for a time of 3 to 5 hours, preferably 3.5 to 4.5 hours.
[0030] In the present invention, the binder in step 3) is selected from any one or more of bentonite, silica sol, pseudo-boehmite, polyvinyl alcohol, and polyacrylamide, preferably silica sol.
[0031] In the present invention, the mass proportion of the binder in step 3) to the total mass of carrier-2, binder and extrusion aid is 6% to 14%, preferably 9% to 11%.
[0032] In the present invention, the extrusion aid in step 3) is selected from any one or more of sesbania powder, polyethylene glycol, polycarboxylic acid, and carboxymethyl cellulose, preferably sesbania powder.
[0033] In the present invention, the mass proportion of the extrusion aid in step 3) to the total mass of carrier-2, binder and extrusion aid is 1% to 5%, preferably 2.5% to 3.5%.
[0034] In the present invention, during the kneading process of step 3), the powder (carrier-2, binder and extrusion aid) and water need to be evenly mixed together, and the water-powder ratio is 0.1mL / g to 0.5mL / g, preferably 0.25mL / g to 0.35mL / g.
[0035] In the present invention, the extruder in step 3) is a twin-screw extruder.
[0036] In the present invention, the drying in step 3) is carried out at a temperature of 60 to 100° C., preferably 75 to 85° C., and for a time of 8 to 16 hours, preferably 11 to 13 hours.
[0037] In the present invention, the precious metal in step 4) is selected from any one or more of Pt, Pd, Ru, Rh and Au, and Pd is selected.
[0038] Preferably, the noble metal precursor is selected from soluble salts of noble metals, more preferably any one or more of hydrochlorides, nitrates, and carbonates of noble metals, preferably hydrochlorides.
[0039] In the present invention, the mass ratio of the noble metal precursor to the carrier in step 4) is 1:40 to 1:200, preferably 1:120.
[0040] In the present invention, the hydrothermal impregnation in step 4) is carried out at a temperature of 120 to 200° C., preferably 150 to 170° C., for a time of 8 to 16 hours, preferably 11 to 13 hours.
[0041] The drying temperature is 60-80°C, preferably 68-72°C, and the drying time is 12-24h, preferably 16-20h.
[0042] The calcination temperature is 400-600° C., preferably 480-520° C., and the calcination time is 3-7 hours, preferably 4.5-5.5 hours.
[0043] The present invention also provides a high-strength supported noble metal catalyst prepared by the above method, comprising a high-strength carrier and a noble metal active component supported thereon.
[0044] The catalyst of the present invention has a noble metal dispersion of 50-74%, a pore size of 4-10 nm, and a specific surface area of 100-160 m 2 / g, the catalyst strength is 120~200N / cm.
[0045] The present invention also provides applications of the high-strength supported noble metal catalyst, which includes hydrogenation reaction, methanol oxidation, unsaturated hydrocarbon oxidation, petroleum reforming reaction, and catalytic oxidation of chlorine-containing organic matter and hydrogen chloride.
[0046] Finally, the present invention provides a method for preparing chlorine by catalytic oxidation of hydrogen chloride, wherein the method uses the above-mentioned catalyst of the present invention to carry out catalytic oxidation of hydrogen chloride.
[0047] Preferably, in the method, the molar ratio of hydrogen chloride to oxygen is 1:0.25-1, preferably 1:0.4-0.6; the temperature of the catalytic oxidation reaction process is 280-360°C, preferably 300-310°C, and the pressure is 0.1-0.3 MPaG, preferably 0.15-0.25 MPaG;
[0048] In the method, the catalytic oxidation of hydrogen chloride to produce chlorine is carried out in a fixed bed reactor, and the volume space velocity of hydrogen chloride is 0.6 to 0.7 h -1 .
[0049] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0050] The invention introduces additives into the carrier to improve the electron migration ability and interaction between the carrier and the active component, performs acidification treatment to enhance the acid resistance of the carrier in a high HCl space velocity atmosphere, uses a binder and an extrusion aid to modify its structure to improve the carrier strength, and further adopts a hydrothermal method to impregnate the loaded precious metal to enhance the water resistance of the catalyst active component in high-temperature water vapor, thereby effectively preventing the loss of precious metals, the reduction of carrier strength and the occurrence of pulverization, and finally making the catalyst exhibit excellent HCl oxidation reaction activity and strength.
[0051] The high-strength supported noble metal catalyst of the present invention is applied to the HCl catalytic oxidation reaction to produce chlorine, and has good activity and operation stability. The reaction conversion rate of HCl can be as high as 90% or more, and the catalyst is heated at a space velocity of 6.7h -1At 400℃, after 200 hours of degradation treatment by passing 1 vol% H2O gas, there was no obvious decrease in reaction activity and overall strength. DETAILED DESCRIPTION
[0052] The following is a detailed description of an embodiment of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0053] The sources of the main raw materials in the examples and comparative examples of the present invention are as follows. Other sources are obtained from common commercial channels unless otherwise specified:
[0054] Aluminum chloride, titanium sulfate, zirconium oxychloride, sodium silicate, boric acid, magnesium chloride, zinc chloride, copper sulfate, ammonia water, ethanol, phosphoric acid, citric acid, formic acid, acetic acid, hypochlorous acid, bentonite (suitable for medium and high polar solvents), silica sol (molecular weight 60.08, particle size: 10-30nm, SiO2: 25-30wt% in water), pseudo-boehmite (monoclinic system, layered structure), polyvinyl alcohol (hydrolysis degree 88%, average molecular weight 145000-180000), polyacrylamide (anionic, molecular weight: 8-15 million), sesbania powder, polyethylene glycol (average Mn 1500), tartaric acid, carboxymethyl cellulose (viscosity: 800-1200mpa.s, USP grade), PdCl2 (purity: Pd59-60%): Beijing Inokai Technology Co., Ltd.
[0055] The main instrumental analysis methods used in the examples and comparative examples of the present invention are:
[0056] Specific surface analysis tester: ASAP2020, BET from American Mack;
[0057] X-ray fluorescence spectrometer: Fujian Jingxi Instrument Co., Ltd. Epsilon4, XRF;
[0058] Particle strength tester: Taizhou Jiangyan Analytical Instrument Factory KC-4, strength test.
[0059] Fully automatic chemisorption instrument: AutoChemⅡ2920 from Merck Meretic Instruments Co., Ltd., for precious metal dispersion test.
[0060] Example 1
[0061] A method for preparing a high-strength supported noble metal catalyst comprises the following steps:
[0062] 1) First, 13.3 g of aluminum chloride, 115.2 g of titanium sulfate, 32.2 g of zirconium oxychloride and 0.266 g of zinc chloride were dissolved in 500 g of deionized water, and then the mixture was continuously stirred and mixed using a magnetic stirrer, and 0.5 mol / L of ammonia water was added dropwise while stirring to precipitate until the pH value of the solution reached 8, and then the mixture was allowed to stand at room temperature for 12 h and then filtered, and the filtered solid was washed 3 times with water and ethanol respectively, and dried in a 60 ° C oven for 8 h, and finally calcined at 800 ° C for 3 h in a muffle furnace under a nitrogen atmosphere to obtain carrier-1;
[0063] 2) The carrier-1 prepared in step 1) was immersed in a 0.05 mol / L formic acid solution at 20° C. for 4 h at a mass ratio of 1:1, and then taken out and dried in an oven at 60° C. for 3 h to obtain a pretreated carrier-2;
[0064] 3) Carrier-2, 2.68g bentonite, 0.45g polyethylene glycol and water were mixed and kneaded evenly according to a water-powder ratio of 0.1mL / g, and then loaded into a twin-screw extruder to form a film, and placed in an oven at 60°C for 8h to obtain carrier-3;
[0065] 4) Finally, 160 mL of water was added to the carrier-3 and the precursor solution containing 1.04 g of PdCl2 to mix evenly to obtain a mixed solution, which was then transferred to a 200 mL hydrothermal autoclave lining and hydrothermally impregnated in an oven at 120°C for 8 h. After drying in an oven at 60°C for 12 h, the solution was calcined at 400°C for 3 h in a muffle furnace under a nitrogen atmosphere to obtain a high-strength supported precious metal catalyst.
[0066] The physical properties of the catalyst are as follows: Pd loading is 1.48wt%, Pd metal dispersion is 50%, pore size is 7.4nm, specific surface area is 131m 2 / g, catalyst strength 176N / cm.
[0067] The above catalyst is used for the catalytic oxidation of hydrogen chloride to produce chlorine in a fixed bed reactor. The catalytic reaction conditions are: reaction temperature 328°C, reaction pressure 0.1MPa, molar ratio of hydrogen chloride to oxygen 1:0.5, volumetric space velocity of hydrogen chloride 0.67h -1 The initial reaction time was 90% for the conversion of hydrogen chloride.
[0068] Evaluation of catalyst degradation environmental stability: Catalyst at a space velocity of 6.7h -1 , at 400 ° C, 1 vol% H2O content of HCl gas was introduced for degradation treatment for 200 hours, and then the temperature was reduced to 328 ° C, and the reaction was continued under the above conditions. The measured hydrogen chloride conversion rate was 86.8%, and the reaction activity decreased by 3.2% compared with before and after. The catalyst strength after the reaction was 167 N / cm, and the strength decreased by 5.1% compared with before and after.
[0069] Example 2
[0070] A method for preparing a high-strength supported noble metal catalyst comprises the following steps:
[0071] 1) First, 20 g of aluminum chloride, 96 g of titanium sulfate, 24.2 g of zirconium oxychloride and 0.4 g of boric acid were dissolved in 500 g of deionized water, and then the mixture was continuously stirred and mixed using a magnetic stirrer, and 0.5 mol / L of ammonia water was added dropwise while stirring to precipitate until the pH value of the solution was 8.5, and then the mixture was allowed to stand for 15 h at room temperature and then filtered, and the filtered solid was washed 3 times with water and ethanol respectively, and dried in an oven at 65 ° C for 10 h, and finally calcined at 900 ° C for 4 h in an argon atmosphere in a muffle furnace to obtain carrier-1;
[0072] 2) The carrier-1 prepared in step 1) was immersed in a 0.05 mol / L acetic acid solution at 22° C. for 6 h at a mass ratio of 1:1.5, and then taken out and dried in an oven at 65° C. for 3.5 h to obtain a pretreated carrier-2;
[0073] 3) Carrier-2, 3.30 g pseudo-boehmite, 0.83 g sesbania powder and water were mixed and kneaded evenly at a water-powder ratio of 0.2 mL / g, and then loaded into a twin-screw extruder to form a film, and placed in an oven at 70° C. to dry for 10 h to obtain carrier-3;
[0074] 4) Finally, 160 mL of water was added to the carrier-3 and the precursor solution containing 0.46 g of PdCl2 to mix evenly to obtain a mixed solution, which was then transferred to a 200 mL hydrothermal autoclave lining and hydrothermally impregnated in an oven at 140 °C for 10 h. After drying in an oven at 65 °C for 15 h, the solution was calcined at 450 °C for 4 h in an argon atmosphere in a muffle furnace to obtain a high-strength supported precious metal catalyst.
[0075] The physical properties of the catalyst are as follows: Pd loading is 0.74wt%, Pd metal dispersion is 63%, pore size is 9.2nm, specific surface area is 145m 2 / g, catalyst strength 189N / cm.
[0076] The above catalyst is used for the catalytic oxidation of hydrogen chloride to produce chlorine in a fixed bed reactor. The catalytic reaction conditions are: reaction temperature 309°C, reaction pressure 0.1MPa, molar ratio of hydrogen chloride to oxygen 1:0.5, volumetric space velocity of hydrogen chloride 0.67h -1 The initial reaction time was 90% for the conversion of hydrogen chloride.
[0077] Evaluation of catalyst degradation environmental stability: Catalyst at a space velocity of 6.7h -1, at 400 ° C, 1 vol% H2O content of HCl gas was introduced for degradation treatment for 200 hours, and then the temperature was reduced to 309 ° C. The reaction was continued under the above conditions. The hydrogen chloride conversion rate was measured to be 88.6%. The reaction activity decreased by 1.4% compared with before and after. The catalyst strength after the reaction was 186 N / cm, and the strength decreased by 1.6% compared with before and after.
[0078] Example 3
[0079] A method for preparing a high-strength supported noble metal catalyst comprises the following steps:
[0080] 1) First, 26.6 g of aluminum chloride, 76.8 g of titanium sulfate, 16.1 g of zirconium oxychloride and 0.532 g of sodium silicate were dissolved and mixed in 500 g of deionized water, and then the mixture was continuously stirred and mixed using a magnetic stirrer, and 0.5 mol / L of ammonia water was added dropwise while stirring to precipitate until the pH value of the solution reached 9, and then the mixture was allowed to stand at room temperature for 18 h and then filtered, and the filtered solid was washed 3 times with water and ethanol respectively, and dried in a 70 ° C oven for 12 h, and finally calcined at 1000 ° C for 5 h in an air atmosphere in a muffle furnace to obtain carrier-1;
[0081] 2) The carrier-1 prepared in step 1) was immersed in a 0.05 mol / L hypochlorous acid solution at 25° C. for 8 h at a mass ratio of 1:2, and then taken out and dried in an oven at 70° C. for 4 h to obtain a pretreated carrier-2;
[0082] 3) Carrier-2, 3.78 g silica sol, 1.13 g carboxymethyl cellulose and water were mixed at a water-to-powder ratio of 0.3 mL / g, and then loaded into a twin-screw extruder to form a strip, and then placed in an oven at 80° C. to dry for 12 h to obtain carrier-3;
[0083] 4) Finally, 160 mL of water was added to the carrier-3 and the precursor solution containing 0.27 g of PdCl2 to mix evenly to obtain a mixed solution, which was then transferred to a 200 mL hydrothermal autoclave lining and hydrothermally impregnated in an oven at 160°C for 12 h. After drying in an oven at 70°C for 18 h, the solution was calcined at 500°C for 5 h in an argon atmosphere in a muffle furnace to obtain a high-strength supported precious metal catalyst.
[0084] The physical properties of the catalyst are as follows: Pd loading is 0.5wt%, Pd metal dispersion is 74%, pore size is 10nm, specific surface area is 160m 2 / g, catalyst strength 200N / cm.
[0085] The catalyst is used for the catalytic oxidation of hydrogen chloride to produce chlorine in a fixed bed reactor. The catalytic reaction conditions are: reaction temperature 296°C, reaction pressure 0.1MPa, molar ratio of hydrogen chloride to oxygen 1:0.5, volumetric space velocity of hydrogen chloride 0.67h -1 The initial reaction time was 90% for the conversion of hydrogen chloride.
[0086] Evaluation of catalyst degradation environmental stability: Catalyst at a space velocity of 6.7h -1 , at 400 ° C, 1 vol% H2O content of HCl gas was introduced for degradation treatment for 200 hours, and then the temperature was reduced to 296 ° C. The reaction was continued under the above conditions. The hydrogen chloride conversion rate was measured to be 89.5%. The reaction activity decreased by 0.5% compared with before and after. The catalyst strength after the reaction was 199 N / cm, and the strength decreased by 0.5% compared with before and after.
[0087] Example 4
[0088] A method for preparing a high-strength supported noble metal catalyst comprises the following steps:
[0089] 1) First, 33.2 g of aluminum chloride, 57.6 g of titanium sulfate, 12.1 g of zirconium oxychloride and 0.664 g of magnesium chloride were dissolved and mixed in 500 g of deionized water, and then the mixture was continuously stirred and mixed using a magnetic stirrer, and 0.5 mol / L of ammonia water was added dropwise while stirring to precipitate until the pH value of the solution was 9.5, and then the mixture was allowed to stand at room temperature for 21 h and then filtered, and the filtered solid was washed 3 times with water and ethanol respectively, and dried in a 75 ° C oven for 14 h, and finally calcined at 1100 ° C in a helium atmosphere in a muffle furnace for 6 h to obtain carrier-1;
[0090] 2) The carrier-1 prepared in step 1) was immersed in a 0.05 mol / L phosphoric acid solution at 27° C. for 10 h at a mass ratio of 1:2.5, and then taken out and dried in an oven at 75° C. for 4.5 h to obtain a pretreated carrier-2;
[0091] 3) Carrier-2, 4.23 g polyvinyl alcohol, 1.41 g sesbania powder and water were mixed at a water-powder ratio of 0.4 mL / g, and then loaded into a twin-screw extruder to form a film, and then placed in an oven at 90° C. to dry for 14 h to obtain carrier-3;
[0092] 4) Finally, 160 mL of water was added to the carrier-3 and the precursor solution containing 0.19 g of PdCl2 to mix evenly to obtain a mixed solution, which was then transferred to a 200 mL hydrothermal autoclave lining and hydrothermally impregnated in an oven at 180°C for 14 h. After drying in an oven at 75°C for 21 h, the solution was calcined at 550°C for 6 h in an argon atmosphere in a muffle furnace to obtain a high-strength supported precious metal catalyst.
[0093] The physical properties of the catalyst are as follows: Pd loading is 0.37wt%, Pd metal dispersion is 66%, pore size is 8.5nm, specific surface area is 135m 2 / g, catalyst strength 185N / cm.
[0094] The above catalyst is used for the catalytic oxidation of hydrogen chloride to produce chlorine in a fixed bed reactor. The catalytic reaction conditions are: reaction temperature 316°C, reaction pressure 0.1MPa, molar ratio of hydrogen chloride to oxygen 1:0.5, volumetric space velocity of hydrogen chloride 0.67h -1 The initial reaction time was 90% for the conversion of hydrogen chloride.
[0095] Evaluation of catalyst degradation environmental stability: Catalyst at a space velocity of 6.7h -1 , at 400 ° C, 1 vol% H2O content of HCl gas was introduced for degradation treatment for 200 hours, and then the temperature was reduced to 316 ° C, and the reaction was continued under the above conditions. The measured hydrogen chloride conversion rate was 87.7%, and the reaction activity decreased by 2.3% compared with before and after. The catalyst strength after the reaction was 180 N / cm, and the strength decreased by 2.7% compared with before and after.
[0096] Example 5
[0097] A method for preparing a high-strength supported noble metal catalyst comprises the following steps:
[0098] 1) First, 35.9 g of aluminum chloride, 49.9 g of titanium sulfate, 8.0 g of zirconium oxychloride and 0.718 g of copper sulfate were dissolved and mixed in 500 g of deionized water, and then the mixture was continuously stirred and mixed using a magnetic stirrer, and 0.5 mol / L of ammonia water was added dropwise for precipitation while stirring until the pH value of the solution reached 10, and then the mixture was allowed to stand for 24 h at room temperature and then filtered, and the filtered solid was washed 3 times with water and ethanol respectively, and dried in an oven at 80 ° C for 16 h, and finally calcined at 1200 ° C for 7 h in an oxygen atmosphere in a muffle furnace to obtain carrier-1;
[0099] 2) The carrier-1 prepared in step 1) was immersed in a 0.05 mol / L citric acid solution at 30° C. for 12 h at a mass ratio of 1:3, and then taken out and dried in an oven at 80° C. for 5 h to obtain a pretreated carrier-2;
[0100] 3) Carrier-2, 4.77 g polyacrylamide, 1.7 g polycarboxylic acid and water were mixed at a water-powder ratio of 0.5 mL / g, and then loaded into a twin-screw extruder to form a strip, and then placed in an oven at 100° C. to dry for 16 h to obtain carrier-3;
[0101] 4) Finally, 160 mL of water was added to the carrier-3 and the precursor solution containing 0.14 g of PdCl2 to mix evenly to obtain a mixed solution, which was then transferred to a 200 mL hydrothermal autoclave lining and hydrothermally impregnated in an oven at 200 °C for 16 h. After drying in an oven at 80 °C for 24 h, the solution was calcined at 600 °C for 7 h in an argon atmosphere in a muffle furnace to obtain a high-strength supported precious metal catalyst.
[0102] The physical properties of the catalyst are as follows: Pd loading is 0.3wt%, Pd metal dispersion is 53%, pore size is 6.9nm, specific surface area is 128m 2 / g, catalyst strength 173N / cm.
[0103] The above catalyst is used for the catalytic oxidation of hydrogen chloride to produce chlorine in a fixed bed reactor. The catalytic reaction conditions are: reaction temperature 322°C, reaction pressure 0.1MPa, molar ratio of hydrogen chloride to oxygen 1:0.5, volumetric space velocity of hydrogen chloride 0.67h -1 The initial reaction time was 90% for the conversion of hydrogen chloride.
[0104] Evaluation of catalyst degradation environmental stability: Catalyst at a space velocity of 6.7h -1 , at 400 ° C, 1 vol% H2O content of HCl gas was introduced for degradation treatment for 200 hours, and then the temperature was reduced to 322 ° C. The reaction was continued under the above conditions. The hydrogen chloride conversion rate was measured to be 87%, and the reaction activity decreased by 3.0% compared with before and after. The catalyst strength after the reaction was 166 N / cm, and the strength decreased by 4% compared with before and after.
[0105] Comparative Example 1
[0106] A method for preparing a high-strength supported noble metal catalyst comprises the following steps:
[0107] 1) First, 26.6 g of aluminum chloride, 76.8 g of titanium sulfate, and 16.1 g of zirconium oxychloride were dissolved and mixed in 500 g of deionized water, and then a magnetic stirrer was used to continuously stir and mix them evenly, and 0.5 mol / L of ammonia water was added dropwise while stirring to precipitate until the pH value of the solution reached 9, and then the solution was allowed to stand for 18 h at room temperature and then filtered, and the filtered solid was washed 3 times with water and ethanol respectively, and dried in a 70 ° C oven for 12 h, and finally calcined at 1000 ° C for 5 h in an air atmosphere in a muffle furnace to obtain carrier-1;
[0108] 2) The carrier-1 prepared in step 1) was immersed in a 0.05 mol / L hypochlorous acid solution at 25° C. for 8 h at a mass ratio of 1:2, and then taken out and dried in an oven at 70° C. for 4 h to obtain a pretreated carrier-2;
[0109] 3) Carrier-2, 3.72 g silica sol, 1.12 g carboxymethyl cellulose and water were mixed at a water-to-powder ratio of 0.3 mL / g, and then loaded into a twin-screw extruder to form a strip, and then placed in an oven at 80° C. to dry for 12 h to obtain carrier-3;
[0110] 4) Finally, 160 mL of water was added to the carrier-3 and the precursor solution containing 0.27 g of PdCl2 to mix evenly to obtain a mixed solution, which was then transferred to a 200 mL hydrothermal autoclave lining and hydrothermally impregnated in an oven at 160°C for 12 h. After drying in an oven at 70°C for 18 h, the solution was calcined at 500°C for 5 h in an argon atmosphere in a muffle furnace to obtain a high-strength supported precious metal catalyst.
[0111] The physical properties of the catalyst are as follows: Pd loading is 0.5wt%, Pd metal dispersion is 44%, pore size is 5.1nm, specific surface area is 120m 2 / g, catalyst strength 142N / cm.
[0112] The above catalyst is used for the catalytic oxidation of hydrogen chloride to produce chlorine in a fixed bed reactor. The catalytic reaction conditions are: reaction temperature 335°C, reaction pressure 0.1MPa, molar ratio of hydrogen chloride to oxygen 1:0.5, volumetric space velocity of hydrogen chloride 0.67h -1 The initial reaction time was 90% for the conversion of hydrogen chloride.
[0113] Evaluation of catalyst degradation environmental stability: Catalyst at a space velocity of 6.7h -1 , at 400 ° C, 1 vol% H2O content of HCl gas was introduced for degradation treatment for 200 hours, and then the temperature was reduced to 335 ° C. The reaction was continued under the above conditions. The hydrogen chloride conversion rate was measured to be 83%. The reaction activity decreased by 7% compared with before and after. The catalyst strength after the reaction was 130 N / cm, and the strength decreased by 8.4% compared with before and after.
[0114] Comparative Example 2
[0115] A method for preparing a high-strength supported noble metal catalyst comprises the following steps:
[0116] 1) First, 26.6 g of aluminum chloride, 76.8 g of titanium sulfate, 16.1 g of zirconium oxychloride and 0.532 g of sodium silicate were dissolved and mixed in 500 g of deionized water, and then the mixture was continuously stirred and mixed using a magnetic stirrer, and 0.5 mol / L of ammonia water was added dropwise while stirring to precipitate until the pH value of the solution reached 9, and then the mixture was allowed to stand at room temperature for 18 h and then filtered, and the filtered solid was washed 3 times with water and ethanol respectively, and dried in a 70 ° C oven for 12 h, and finally calcined at 1000 ° C for 5 h in an air atmosphere in a muffle furnace to obtain carrier-1;
[0117] 2) The carrier-1 prepared in step 1) was immersed in a 0.05 mol / L hypochlorous acid solution at 25° C. for 8 h at a mass ratio of 1:2, and then taken out and dried in an oven at 70° C. for 4 h to obtain a pretreated carrier-2;
[0118] 3) Carrier-2, 3.78 g silica sol, 1.13 g carboxymethyl cellulose and water were mixed at a water-to-powder ratio of 0.3 mL / g, and then loaded into a twin-screw extruder to form a strip, and then placed in an oven at 80° C. to dry for 12 h to obtain carrier-3;
[0119] 4) Finally, the carrier-3 and the precursor solution containing 0.27 g PdCl2 were impregnated with equal volumes at room temperature for 12 h, dried in an oven at 70°C for 18 h, and then calcined at 500°C for 5 h in an argon atmosphere in a muffle furnace to obtain a high-strength supported precious metal catalyst.
[0120] The physical properties of the catalyst are as follows: Pd loading is 0.5wt%, Pd metal dispersion is 35%, pore size is 6.2nm, specific surface area is 125m 2 / g, catalyst strength 155N / cm.
[0121] The catalyst is used for the catalytic oxidation of hydrogen chloride to produce chlorine in a fixed bed reactor. The catalytic reaction conditions are: reaction temperature 345°C, reaction pressure 0.1MPa, molar ratio of hydrogen chloride to oxygen 1:0.5, volumetric space velocity of hydrogen chloride 0.67h -1 The initial reaction time was 90% for the conversion of hydrogen chloride.
[0122] Evaluation of catalyst degradation environmental stability: Catalyst at a space velocity of 6.7h -1 , at 400 ° C, 1 vol% H2O content of HCl gas was introduced for degradation treatment for 200 hours, and then the temperature was reduced to 345 ° C, and the reaction was continued under the above conditions. The measured hydrogen chloride conversion rate was 80%, and the reaction activity decreased by 10% compared with before and after. The catalyst strength after the reaction was 144 N / cm, and the strength decreased by 7.1% compared with before and after.
[0123] Compared with common noble metal catalysts, the high-strength supported noble metal catalyst prepared by the method of the present invention has significantly improved reaction activity, strength, water resistance and stability, and can maintain a reaction space velocity of 6.7h -1 , at 400°C, after 200h of degradation treatment by passing HCl gas with a H2O content of 1 vol%, the reaction activity and catalyst strength did not show a significant decrease. Among them, Example 3 showed the best strength and reaction performance. The HCl reaction conversion rate at 296°C can be maintained at 90%, and the catalyst strength remains unchanged.
[0124] Although the specification has been described in detail and specifically for the high-strength supported noble metal catalyst and its preparation and application, it is obvious that researchers in the field will still infer other obvious changes and contents after reading the description of the previous specification. Therefore, the present invention is not limited to the specific embodiments described herein, and all contents that do not violate the spirit and scope of the present invention should also be included in this application.
Claims
1. A method for preparing a high-strength supported noble metal catalyst, comprising the following steps: 1) dissolving aluminum chloride, titanium sulfate, zirconium oxychloride and additives in a solvent, adding ammonia water for precipitation, controlling the pH value of the solution, standing for aging, filtering, washing, drying and calcining to obtain carrier-1; 2) soaking the carrier-1 prepared in step 1) in a weakly acidic solution, taking it out and drying it to obtain a pretreated carrier-2; 3) Carrier-2, binder, extrusion aid and water are mixed and kneaded uniformly, and then loaded into a twin-screw extruder, molded using a template, and dried to obtain carrier-3; 4) Finally, water is added to the carrier-3 and the noble metal precursor solution to mix evenly to obtain a mixed solution, which is then transferred to the inner lining of a hydrothermal reactor, hydrothermally impregnated in a high-temperature oven, and then dried and air-baked to obtain a high-strength supported noble metal catalyst.
2. The preparation method according to claim 1, characterized in that The mass ratio of aluminum chloride, titanium sulfate and zirconium oxychloride in step 1) is 0.41-4.49:3.58-6.24:1, preferably 1.6-1.7:4.7-4.8:1; and / or, the additive in step 1) is selected from any one or more of sodium silicate, boric acid, magnesium chloride, zinc chloride and copper sulfate, preferably sodium silicate; and / or, the mass ratio of the additive in step 1) to aluminum chloride is 1:45-55; and / or, the solvent in step 1) is water, and the concentration of ammonia water is 0.45-0.55 mol / L.
3. The preparation method according to claim 1 or 2, characterized in that: The pH value of the solution in step 1) is 8-10, preferably 8.5-9.5; and / or, the drying temperature in step 1) is 60-80°C, preferably 68-72°C, and the time is 8-16h, preferably 11-13h; and / or, the calcination temperature is 800-1200°C, preferably 950-1050°C, and the time is 3-7h, preferably 4.5-5.5h.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The weak acid solution in step 2) is selected from any one or more of hypochlorous acid, phosphoric acid, citric acid, formic acid, and acetic acid, preferably hypochlorous acid; the concentration of the weak acid solution is 0.04-0.06 mol / L; and / or the mass ratio of the carrier-1 to the weak acid solution is 1:1-3, preferably 1:1.5-2.5; and / or, the soaking in step 2) is at a temperature of 20-30°C, preferably 24-26°C, for 4-12h, preferably 7-9h; and / or, the drying in step 2) is at a temperature of 60-80°C, preferably 68-72°C, for 3-5h, preferably 3.5-4.5h.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The binder in step 3) is selected from any one or more of bentonite, silica sol, pseudo-boehmite, polyvinyl alcohol, and polyacrylamide, preferably silica sol; and / or, the extrusion aid in step 3) is selected from any one or more of sesbania powder, polyethylene glycol, polycarboxylic acid, and carboxymethyl cellulose, preferably sesbania powder; and / or, the mass proportion of the binder in step 3) to the total mass of carrier-2, binder and extrusion aid is 6% to 14%, preferably 9% to 11%; and / or, the mass proportion of the extrusion aid in step 3) to the total mass of carrier-2, binder and extrusion aid is 1% to 5%, preferably 2.5%-3.5%.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step 3), the drying temperature is 60-100°C, preferably 75-85°C, and the time is 8-16h, preferably 11-13h; and / or, in step 4), the noble metal is selected from any one or more of Pt, Pd, Ru, Rh and Au, all of which are Pd; and / or, the noble metal precursor is selected from soluble salts of noble metals, more preferably any one or more of hydrochlorides, nitrates and carbonates of noble metals, preferably hydrochlorides; and / or, in step 4), the mass ratio of the noble metal precursor to the carrier is 1:40-1:200, preferably 1:
120.
7. The preparation method according to any one of claims 1 to 6, characterized in that: Step 4) The hydrothermal impregnation is carried out at a temperature of 120 to 200°C, preferably 150 to 170°C, for 8 to 16 hours, preferably 11 to 13 hours; and / or the drying is carried out at a temperature of 60 to 80°C, preferably 68 to 72°C, for 12 to 24 hours, preferably 16 to 20 hours; and / or the calcination is carried out at a temperature of 400 to 600°C, preferably 480 to 520°C, for 3 to 7 hours, preferably 4.5 to 5.5 hours.
8. A high-strength supported noble metal catalyst prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the high-strength supported noble metal catalyst prepared by the preparation method according to any one of claims 1 to 7 or the high-strength supported noble metal catalyst according to claim 8 in hydrogenation reactions, methanol oxidation, unsaturated hydrocarbon oxidation, petroleum reforming reactions, and catalytic oxidation reactions of chlorinated organic matter and hydrogen chloride.
10. A method for preparing chlorine by catalytic oxidation of hydrogen chloride, wherein the catalyst is a high-strength supported precious metal catalyst prepared by the preparation method according to any one of claims 1 to 7 or a high-strength supported precious metal catalyst according to claim 8, and the molar ratio of hydrogen chloride to oxygen is 1:0.25-1, preferably 1:0.4-0.6; the temperature of the catalytic oxidation reaction process is 280-360°C, preferably 300-310°C, and the pressure is 0.1-0.3 MPaG, preferably 0.15-0.25 MPaG.
Citation Information
Cited By
Forming method of Ru-based catalyst for catalyzing hydrogenation of 2, 4-dinitrotoluene to prepare 1-methyl-2, 4-cyclohexanediamine
CN120037902A
Honeycomb type hydrolysis catalyst suitable for fine desulfurization of coal gas and preparation method of honeycomb type hydrolysis catalyst
CN120790129A
